EVALUASI PERTUMBUHAN POHON Di LOKASI REVEGETASI LAHAN PASCA TAMBANG PT. GENBA MULTIMINERAL DESA MOLINO KECAMATAN PETASIA TIMUR KABUPATEN MOROWALI UTARA - Oktavian S; Adam Malik; Abdul Wahid (Jurnal Warta Rimba, 2019)
Mining is one of the activities of management and utilization of natural resources as an effort to fulfill human needs and is the largest contributor to foreign exchange, mining business activities in forest areas used to support development have caused environmental damage and must be reclaimed immediately. This study aims to describe the status of tree growth in post-mining land and evaluate the causes of health problems in tree growth in post-mining land. The method used in this study uses two blocks of objects carried out at one location, namely in block 7. The parameters measured in identifying the status of this growth are plant diameter, plant height, percent plant growth, percent health of plants and soil samples. The types of plants observed in this study were sengon (Paraserianthes Falcateria), lamtoro (Leucaena Leucocephala). The results showed that based on two observation blocks, namely block a with lamtoro and block b with sengon plants, the percent growth and the best percent health were in block a where percent grew by 83% and percent health of the plant by 100%. On the other hand, in blocks of b percent, plant growth is only 37% and percent of plant health is 00.0%. Based on the lab results on soil sampling from each block, block B has a very low nutrient content compared to block a. The results of soil analysis on the observed blocks showed that there was a low nutrient value in nitrogen (N), potassium (K), and phosphorus (P).Keywords: post-mining land, nutrient deficiency, plant growth.